Hydrogen separation through pi/ncc carbon membrane: effect of stabilization environment and heating rates - Norazlianie, Sazali; K., Kadirgama; Wan Norharyati, Wan Salleh; F. E., C. Othman; N. H., Ismail; A. F., Ismail (2018)
separation of hydrogen with nitrogen. TCMs were fabricated by dip coating process using P84 copolyimide as a main precursor with blending of Nanocrysttaline cellulose (NCC) as an additives. Previously, it was shown that changing the time, temperature, or environment of the carbonization protocol for a commercially available PI/NCC altered the final properties of the carbons produced. A large variety of TCMs for gas separation have been developed by simple carbonization of a PI/NCC deposited on a ceramic tubular support. In this study, heating rates (1, 3, 5, and 7 oC/min) and stabilization environment (Argon, Nitrogen, and Helium) were investigated and the effect on permeation were determined for all resultant TCMs. In recent study, the modifications on the carbonization parameters such as stabilization conditions and heating rates during fabrication of PI/NCC-based carbon membranes could affect their gas separation performance. It was observed that stabilization under Argon environment produced carbon membranes with high separation performance while heating rates of 3oC/min improved the membrane selectivity but reduced the membrane’s permeability. In literature, the rate of evolution of the volatile compounds can be determined by carbonization heating rate as it is believed could affect the microstructure of the carbon membranes [1]. The variation in carbonization heating rates have showed different gas separation results on the PI/NCC carbon membranes as represented in Table 1. The data obtained showed an average value from at least three different PI/NCC carbon membranes with small error analysis of ±10% for both selectivity and permeance value.